Rancang Bangun Sistem Informasi Penjualan Ritel Untuk Usaha Mikro dan Kecil Berbasis Web - Permadi, Ageng; Amelia, Tan; Wulandari, Sri Hariani Eko (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
One type of business that a lot of work at the Indonesian population is in the form of retail (Soliha, 2008). Retail in Indonesia is divided into two, namely traditional retail and modern retail. Traditional retail itself in the category of Usaha Mikro Kecil dan Menengah (UMKM). Retail Indonesian population spread in the community thrives. However, intense competition, especially in the face of large modern retailers, traditional retailers are making in a less favorable position. The problem faced by traditional retailers are; (1) the owner can not determine sales trends; (2) purchase a product that is not sold in large quantities; (3) the difficulty of knowing the available stock; (4) does not have the data history of sales transactions; (5) often experience problems in the procurement costs of information technology devices; The solution to the above problems is an information system retail sales web-based that can produce information as up to date as sales turnover, the products most frequently purchased by customers, products sold less that needs to be promoted, benefits and can promote products sold in the form of a web product catalog. All the information can be used as a basis for business owners in making decisions for managing merchandise products as quickly as it can be accessed anytime, anywhere through the Internet.